Enhanced Oral Bioavailability of β-Caryophyllene in Healthy Subjects Using the VESIsorb® Formulation Technology, a Novel Self-Emulsifying Drug Delivery System (SEDDS) - Mödinger, Yvonne; Knaub, Katharina; Dharsono, Tanita; Wacker, Roland; Meyrat, Remo; Land, M. Hunter; Petraglia, Anthony L.; Schön, Christiane (Molecules (Basel, Switzerland), 2022)
β-Caryophyllene (BCP), a common constituent of many spice and food plants, is gaining increased attention due to recent research identifying numerous potential health benefits. Due to limited oral bioavailability observed in preclinical models, the described benefits of BCP may be maximized by using a suitable delivery system. Additionally, human pharmacokinetics (PK) remain unknown. This study evaluates the relative oral bioavailability of BCP formulated in a self-emulsifying drug delivery system (SEDDS) based on VESIsorb® formulation technology (BCP-SEDDS) compared to BCP neat oil. Hence, a randomized, double-blind, cross-over design, single oral dose study (100 mg BCP) in 24 healthy subjects (12 men/12 women) was performed under fasting conditions. Pharmacokinetic parameters were analyzed from individual concentration-time curves. The data show that BCP-SEDDS resulted in a 2.2/2.0-fold increase in AUC0–12h/AUC0–24h and a 3.6-fold increase in Cmax compared to BCP neat oil. Moreover, BCP was absorbed faster from BCP-SEDDS (Tmax: 1.43 h) compared to BCP neat oil (Tmax: 3.07 h). Gender analysis revealed that there is no significant difference between men and women for both the investigated formulations and all investigated PK endpoints. In conclusion, BCP-SEDDS offers a well-tolerated and effective oral delivery system to significantly enhance the oral bioavailability of BCP in humans.